Network-Based Language Teaching at The State University of Surabaya - Fauris Zuhri (PAROLE: Journal of Linguistics and Education, 2013)
This paper discusses the network-based language teaching in the State University of Surabaya. Network-based language teaching (NBLT) refers specifically to the pedagogical use of computers connected in either local or global networks, allowing one-to-one, one-to-many, and many-to-many communication. This research explores what happens when learners are brought together with texts, media, and other speakers of the language in computer-mediated contexts of interaction in English class.   Makalah ini membahas tentang pembelajaran bahasa berbasis jaringan di Universitas Negeri Surabaya, yang mengacu secara spefisik terhadap penggunaan komputer secara pedagogis yang lebih dikaitkan dengan jaringan global atau lokal, seperti komunikasi antar seseorang, seseorang dengan banyak orang, dan antar banyak orang. Kajian ini mengeksplorasi apa yang berkembang ketika mahasiswa berinteraksi dengan teks, media, dan penutur bahasa asing dalam konteks berinteraksi dengan menggunakan media komputer.